(untitled) - Hill, Charles Evan; (1956-...) (U.S.A., 2001)
Regnum Caelorum explores the largely overlooked connection in early Christian thought between understandings of the millennium and the intermediate state of the soul after death. Charles Hill traces Christian views of the soul's fate in Jewish texts, the New Testament, and in early Christian writers through the mid-third century A.D.
Keywords: Eschatologie